The effectiveness of three models ((Gest _, Trajest_, Eddie and Shire)) in achieving geography subjects for fourth literary students - ABOOD, ALI MOHAN; ABD, AL-HARETH SHAKIR (International Journal of Psychosocial Rehabilitation, 2020)
The current study is clear from the knowledge of the effectiveness of three teaching models (Guest), (Trajest) and (Structural Learning) in achieving geography for fourth literary students, by verifying the validity of the following zero hypothesis ((There is no statistically significant difference when Level (0,05) between the average scores of students of the three experimental groups, the first experimental group that studies the course of geographic foundations and their techniques in the (GST) model, the second experimental group that studies with the Trajest model, and the third experimental group that studies the same subject with the (constructive learning) model in the achievement test Al-Baaddi)) Heading for the fourth literary students in the Directorate of Education in the province of Baghdad, the second Rusafa for the academic year 2018/2019, by teaching the first, second and third semester of geographic foundations and their techniques, the study sample reached (69) students distributed over three divisions of three experimental groups, the researchers followed the research method The experimental tool was the study of the post-achievement test, whose paragraphs were prepared from a multiple choice type and reached (40) test items after the validity of the tool was extracted by the experts and the stability of the tool in the Fakronbach equation. The statistical package for social sciences (spss) was used to extract the results For the study, the results of the current study showed that the three teaching models are effective in increasing the level of academic achievement compared to their academic achievement before conducting the experiment, and that these three teaching models help fourth literary students reach themselves to levels of knowledge, understanding, and application, as well as levels of analysis, composition, and evaluation, and in In light of the results of the current study, the researchers recommend adopting modern teaching models, especially the GST model, the Trajest model, and the constructive learning model in teaching subjects of geographic foundations and their techniques in fourth-grade literary students, and informing teachers of a Use geography and its techniques on the steps of these teaching models to use when teaching their subjects.